The predictors of habitual behavior in using mobile phone among university students - Ibrahim, Norasyikin; Mohd Ayub, Ahmad Fauzi; Md. Khambari, Mas Nida (Nextgen Research Publication, 2016)
The use of technology in academic activities, particularly in higher education institutions is one thing in common and undeniable. Entering the era of information technology without borders, the use of technology such as computers, laptops, tablets, mobile phones and so on are seen as essential roles to assist educational activities. Therefore, the utilization has become the norm among instructors and students in higher education institutions. Through previous studies, the terms of norms often referred to habitual behavior or automatically behavior. This study focused on three of independent variables from UTAUT’s model (performance expectancy, effort expectancy and social influences) to predict students’ habitual behavior in higher education in the use of mobile phone. This study involved 393 of undergraduates’ student and was conducted entirely in Universiti Putra Malaysia (UPM), Serdang. The results of data analysis revealed all the independent variables have significant effect on habitual behaviour.